Constraints on Venus Lightning From Akatsuki's First 3 Years in Orbit. Issue 14 (17th July 2019) - Lorenz, Ralph D.; Imai, Masataka; Takahashi, Yukihiro; Sato, Mitsuteru; Yamazaki, Atsushi; Sato, Takao M.; Imamura, Takeshi; Satoh, Takehiko; Nakamura, Masato
Abstract: Observations by the Lightning and Airglow Camera on Japan's Venus Climate Orbiter "Akatsuki" over its first 3 years in orbit are reported. Forty‐two opportunities during low‐altitude nightside passes have accumulated 16.8 hr of observation, yielding an area‐time product of 81.6 ×10 6 km 2 ‐hr, by far the largest at Venus itself to date. No flashes attributable to lightning have been detected, whereas similar observations at Earth would yield thousands of detections. A low flash rate of 0.005 per million km 2 ‐hr indicated in ground‐based observations is not excluded (but would require that there are not many more smaller flashes). The allowable flash rate is incompatible with the much higher rates of bursts recorded by magnetic and electric field sensors at Venus, indicating that electrical discharges at Venus lack optical emission or that the electromagnetic detections have a nonlightning explanation or both. Key Points: Nondetection in 42 observations by a dedicated flash detector on Akatsuki suggests a Venus lightning rate > 1, 000 lower than Earth Result is compatible with zero flashes, with claimed ground‐based detections or with lightning that is highly clustered in space or time Nondetection is incompatible with the rate of whistler mode radio waves, suggesting that their origin is not associated with optical flashes